Mobilization, Mass Perceptions, and (Dis)information: "New" and "Old" Media Consumption Patterns and Protest. (April 2021) - Onuch, Olga; Mateo, Emma; Waller, Julian G.
When people join in moments of mass protest, what role do different media sources play in their mobilization? Do the same media sources align with positive views of mass mobilizations among the public in their aftermath? And, what is the relationship between media consumption patterns and believing disinformation about protest events? Addressing these questions helps us to better understand not only what brings crowds onto the streets, but also what shapes perceptions of, and disinformation about mass mobilization among the wider population. Employing original data from a nationally representative panel survey in Ukraine (Hale, Colton, Onuch, & Kravets, 2014 ) conducted shortly after the 2013–2014 EuroMaidan mobilization, we examine patterns of media consumption among both participants and non-participants, as well as protest supporters and non-supporters. We also explore variation in media consumption among those who believe and reject disinformation about the EuroMaidan. We test hypotheses, prominent in current protest literature, related to the influence of "new" (social media and online news) and "old" media (television) on protest behavior and attitudes. Making use of the significance of 2014 Ukraine as a testing ground for Russian disinformation tactics, we also specifically test for consumption of Russian-owned television. Our findings indicate that frequent consumption of "old" media, specifically Russian-owned television, is significantly associated with both mobilization in and positive perceptions of protest and is a better predictor of believing "fake news" than consuming "new" media sources.